Job Satisfaction among the Nurses Working in Government and Private Hospital in Eastern Part of Nepal (The Mega Journal, 2024)
Nursing is a profession which directly deals with the health of the human being. It requires competence, compassion and genuine commitment. So, job satisfaction among the nurses remains the matter of concern because it directly impacts the quality of patient care. The objective of the Study is to assess the level of satisfaction among the nurses.A descriptive Cross-Sectional study was conducted by using self-administered questionnaire among 200 nurses working in different Governmental and Private Hospital in Eastern Part of Nepal. Data was collected from 2080/1/1/ to 2080/6 30. Job Satisfaction was measured by using five-point Likert scale type questionnaire. Descriptive statistics; Mean, Standard Deviation, Percentage and inferential statistics co-relation analysis were utilized to examine data and draw meaningful insight. The findings of the study revealed that 54.5% (109) respondents were satisfied with their job and 45.5% (91) respondents were unsatisfied with their job. Based on the weighted mean score satisfaction level was assessed where the weighted mean was 3.105. Finding showed that there is significant relationship of job satisfaction with salary and type of hospital and there is no any relationship of job satisfaction with designation, age, qualification, marital status and work experience. Level of job satisfaction is more in government hospital than the private hospital. There is significant relationship between level of job satisfaction with its different components and there is significant differences in level of job satisfaction among nurses between government and private hospital.The study was aimed to find out the job satisfaction among nurses. Based on the findings more than half of the nurses were satisfied with their job and it is also showed that there is significant relationship of job satisfaction with salary and type of hospital. There are various factors where nurses are not satisfied such as; job security, self-growth and development, salary, working condition and hospital environment. If there are dissatisfied, they may stimulate the nurses to intend to leave their job/centers. For the quality care to the patient in hospital nurses’ source of job dissatisfaction must be addressed and managed.